SYNTHESIS OF ARYL (5-SUBSTITUTED BENZOFURAN-2-YL) CARBAMATE DERIVATIVES AS ANTIMICROBIAL AGENTS - Budhwani, Shankar; Sharma, Shailendra; Kalyane, Navanath (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: Benzofurans are very interesting heterocycles, which are available in nature and show a wide range of pharmacological activities, viz., antifungal, antibacterial, antitumor, antimalarial and antioxidant activity. Methods: A convenient method for the preparation of aryl (5-substituted benzofuran-2-yl) carbamate derivatives 6a-6j has been developed. The target compounds 1-(5-nitrobenzofuran-2-yl)-3-arylurea (6a-6e) and 1-(5-bromobenzofuran-2-yl)-3arylurea (6f-6j) have been prepared by reacting 5-nitrobenzofuran-2-carbonyl azide 5a or 5-bromobenzofuran-2-carbonyl azide 5b with substituted phenols in reasonable overall yields. All the synthesized compounds were characterized using Fourier transform infrared (FTIR), 1H NMR and mass spectrometry and were subjected to antimicrobial screening against two Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), two Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and two fungi (Candida albicans and Aspergillus niger) using two-fold dilution method. Results and Discussion: All the values of FTIR, 1H NMR and mass spectra were found to be prominent. The results indicate that synthesized compound 6i showed potent antimicrobial activity comparable to standard. Conclusion: The detailed synthesis, spectroscopic data, and antimicrobial activities of synthesized compounds were reported. Keywords: Benzofuran, Antibacterial activity, Antifungal activity.